Kepastian Hukum Pengenaan Pajak Bea Perolehan Hak Atas Tanah Dan Bangunan Terhadap Hibah Wasiat (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the regulations related to the collection of the Land and Building Rights Acquisition Duty (BPHTB) on testamentary grants, specifically whether there is legal certainty in the process. The Land and Building Rights Acquisition Duty, based on Article 1 point 1 of Law Number 20 of 2000 Concerning the Land and Building Rights Acquisition Duty in conjunction with Article 1 point 37 of Law Number 1 of 2022 concerning Financial Relations Between the Central Government and Regional Governments, is a tax on the acquisition of land and/or building rights. The imposition of BPHTB indicates a transfer of land rights, as there is a tax that must bepaid by the recipient of the land rights due to a legal event, which is juridically proven by anauthentic deed made by the Land Deed Official (PPAT). Based on this explanation, when connected with Article 49 letter (b) of Law Number 1 of 2022 concerning Financial Relations Between the Central Government and Regional Governments, it states that the tax liability for BPHTB arises on the date the testamentary grant deed is made and signed. However, juridically, a testamentary grant deed does not yet constitute a transfer of rights; rather, it is a unilateral agreement containing a person’s declaration of intent regarding what they wish to happen after their death. The legal ambiguity in Article 49 letter (b) of Law Number 1 of 2022 concerning Financial Relations Between the Central Government and Regional Governments has been subjected to judicial review through the Constitutional Court Decision Number 117/PUU-XXI/2023. This research employs normative juridical methods with data collection techniques based on literature study, consisting of primary and secondary legal materials.